ОСОБИСТІСНО ОРІЄНТОВАНИЙ ПІДХІД У ПРОЦЕСІ ФОРМУВАННЯ ПРОФЕСІЙНОЇ ВІДПОВІДАЛЬНОСТІ МАЙБУТНІХ ПЕДАГОГІВ (Педагогіка вищої та середньої школи, 2004)
This article reveals the essence of personal tentative approach in the process for formulate professional responsibility by future teachers and defines its features. The author reveals the essence of features of personal tentative teaching and actes of organization personal tentative approach in the teaching the course „Pedagogics”.